2018
DOI: 10.1128/iai.00631-17
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the Phosphate Transporter NptA Enhances Staphylococcus aureus Pathogenesis by Improving Phosphate Uptake in Divergent Environments

Abstract: During infection, pathogens must obtain all inorganic nutrients, such as phosphate, from the host. Despite the essentiality of phosphate for all forms of life, how obtains this nutrient during infection is unknown. Differing from, the paradigm for bacterial phosphate acquisition, which has two inorganic phosphate (P) importers, genomic analysis suggested that possesses three distinct P transporters: PstSCAB, PitA, and NptA. While and are expressed in phosphate-replete media, expression of all three transporter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 56 publications
4
46
0
Order By: Relevance
“…PitA is constitutively expressed, while PstSCAB is expressed in response to nutrient limitation. Forcing S. aureus to rely on PstSCAB in phosphate-replete medium results in a reduced growth rate (81). Hence, it is not unreasonable to speculate that, similarly to PitA, MntH is retained because of its greater energy efficiency for the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…PitA is constitutively expressed, while PstSCAB is expressed in response to nutrient limitation. Forcing S. aureus to rely on PstSCAB in phosphate-replete medium results in a reduced growth rate (81). Hence, it is not unreasonable to speculate that, similarly to PitA, MntH is retained because of its greater energy efficiency for the pathogen.…”
Section: Discussionmentioning
confidence: 99%
“…including Escherichia coli and other Enterobacteriaceae, Vibrio cholerae, Mycobacterium tuberculosis, and Streptococcus pneumoniae (11)(12)(13)(14)(15)(16)(17)(18). S. aureus encodes three P i transporters that are important for growth in distinct environments and differentially contribute to staphylococcal pathogenesis ( Fig.…”
mentioning
confidence: 99%
“…S. aureus encodes three P i transporters that are important for growth in distinct environments and differentially contribute to staphylococcal pathogenesis ( Fig. 1) (18). Two of these P i transporters, PstSCAB and PitA, are similar to those found in E. coli, the primary model for the study of bacterial P i acquisition.…”
mentioning
confidence: 99%
“…Invading microbes have to acquire Phosphoric acid from their host. Phosphoric acid transporters were observed in pathogens, including Salmonella Typhimurium , pathogenic Escherichia coli , Enterobacteriaceae , Mycobacterium tuberculosis , Vibrio cholerae , Streptococcus pneumonia and Staphylococcus aureus and closely related to their pathogenicity (Burall et al, ; Darwin & Miller, ; Hava & Camilli, ; Kelliher et al, ; Lamarche, Wanner, Crépin, & Harel, ; Lathem, Crosby, Miller, & Goldman, ; Merrell, Hava, & Camilli, ; Peirs et al, ; Valdivia & Falkow, ).…”
Section: Discussionmentioning
confidence: 99%
“…For most bacteria, inorganic Phosphoric acid (Pi) is the preferred source of Phosphoric acid. Three distinct classes of Pi importers were observed in bacteria: PitA, PstSCAB system and NptA (Kelliher et al, ). Genomic analysis suggested that P. plecoglossicida possesses all of these three distinct Pi transporters.…”
Section: Discussionmentioning
confidence: 99%